[LB.02.31] PROSPECTIVE OBSERVATION ON THE ASSOCIATION OF METABOLIC SYNDROME WITH SUBCLINICAL LEFT VENTRICULAR CHANGES OVER A SIX-YEAR PERIOD. (September 2017) - Kim, S.; Lee, S.; Park, J.; Na, J.; Choi, C.; Lim, H.; Suh, S.; Shin, C.
Abstract : Objective: Although a variety of approaches used for the management of the metabolic syndrome (MetS) have been published in the literature, any longitudinal studies have not yet examined the effect of treating MetS on the cardiovascular system. This study was designed to evaluate whether the reversal of the MetS is associated with the improvement of left ventricular (LV) structure and function. Design and method: Data were collected from 508 participants who were diagnosed with the MetS at 4th follow-up study of Ansan cohort and also took part in 7th follow-up, the first one in 2007–2008 and the second one in 2013–2014. LV structure and function were assessed using conventional echocardiography and tissue Doppler imaging (TDI) at baseline and after six years follow-up. Subjects were classified into two groups, according to the presence of MetS at follow-up visit: reversed MetS and persistent MetS groups. Results: LV mass index was increased (all P < 0.001) and subclinical LV systolic function (TDI Sm) was decreased (all P < 0.01) in both groups over a six-year period. There were no significant differences in changes of LVMI and TDI Sm over time between the two groups. However, significant impairment of LV diastolic function (TDI Em) over six years was observed in the persistent MetS group (P < 0.001), but not in the reversed MetS group (P = 0.139), compared to the baseline. After adjustment for age, gender, and baseline TDI Em, there was a significant difference in change of TDI Em over time between the two groups (P < 0.001). The independent predictors of TDI Em reduction over time were age (β=-0.106, P = 0.028), gender (β=-0.099, P = 0.012), anti-hypertensive medication use (β=-0.082, P = 0.031), and changes in systolic blood pressure (β=-0.122, P = 0.001) and body mass index (β=-0.133, P = 0.005). Conclusions: The reversal of MetS did not accelerate subclinical deterioration of LV diastolic parameter during a six-year follow-up. The progression of LV diastolic dysfunction over time was accompanied by an increase in systolic blood pressure and body mass index.